Challenges of achieving domestic water use efficiency: the role of water demand management in Gweru, Zimbabwe - Madebwe, Victor; Madebwe, Crescentia (2016)
The paper examined the role of water demand management instruments to achieve domestic water use efficiency in Gweru. Household water consumption histories were reconstructed using monthly household water consumption records for 2005 to 2010. Background characteristics of household heads were taken into consideration when analyzing water consumption patterns. To manage water demand the City uses socioeconomic instruments like differential water rate structures, education and reduction in water releases to domestic consumers using mechanical devices. These measures are expected to impact domestic water consumption patterns by curtailing perceived non essential uses of water. Results show that impact of these measures on household water consumption is varied. There is a relationship between income and water consumption. Water consumption in high income residential areas is high due to presence of high water demanding indoor appliances and outdoor activities. Households in low income residential areas react to water price disincentives by restricting consumption to basic needs. To succeed water demand management strategies must be supported by robust institutional, legislative and regulatory frameworks for enforcement of the water demand management instruments.